Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Study on the Heavy Metal Pollution and Distribution of Metal Resistance Genes in the Sediments of the Three Gorges Reservoir Perennial Backwater - Chang Han; Wenjun Yang (Water, Air, & Soil Pollution, 2026)

Study on surface morphology characteristics and tensile properties of non-uniformly corroded stud connectors - Yachuan Kuang; Kui Wang; Zhiwei Peng; Wenjun Li; Tianyu Wang; Huan Chen; Han Ling; Yushuo Hu (Engineering Structures, 2026)

Integration of vertical and lateral erosion in modelling landslide mass flows, debris flows and flash floods - Ruochen Jiang; Wenjun Lu; Shihao Xiao; Xin He; Ruiqiang Bai; Yingyue Han; Mingdong Wei; Dalei Peng; Jian He; Limin Zhang (Journal of Hydrology, 2026)

Rare earth smelting wastewater pollution control and resource recovery: A review - Hualin Zhang; Chenhui Zhang; Huiyuan Guo; Qing Liu; Hexing Han; Wenjun Xiang; Tinggang Li (Journal of Environmental Chemical Engineering, 2026)

Antifouling-antimicrobial medical catheters with negative charge and superhydrophilic surfaces - Yuqi Zhou; Qinsheng Lu; Zhenyu Ren; Qianyun Zhang; Haoran Zhang; Yuruo Zhang; Quanjie Lv; Wenjun Shu; Yijun Han; Linxuan Zhang; Yuhao Cai; Congli Yuan; et al. (Chemical Engineering Journal, 2026)

Physics-informed sensor placement for street canyon wind field reconstruction - Wenjun Jiang; Daniel Ziyue Peng; Bo Liu; Han Peng (Sustainable Cities and Society, 2026)

LC-MS-based metabolomics reveals the In Vivo effects of cognitive formula 1 in rats with Aβ-induced Alzheimer’s disease - Di Wu; Yanling Lin; Wenjun Guo; Zengling Wang; Yan Chang; Jing Yan; Daqing Han; Ke Xiang; Zhen Yang (Experimental Brain Research, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

A cost-effective water cooled PEMFC bipolar plate with metal mesh flow field employing 2D fabrication process - Wenjun Li; Ruonan Ding; Weichang Gu; Wenrong Shi; Yingchao Shang; Liuyuan Han; Yang Liu; Yang Li; Fangyong Yu; Zhen Guo (Chemical Engineering Journal, 2026)

Microwave ablation planning in fatty liver based on fat content-dependent electrical properties - Wenxia Ju; Yikun Hong; Jianbo Zhang; Chunyou Ye; Wenjun Yao; Jijun Han (Journal of Thermal Biology, 2026)

Structural similarity analysis and AI-predicted binding mode of bitter flavonoids in pomelo (Citrus maxima) using HRMS-based metabolomics and molecular fingerprinting - Han Wang; Lu Peng; Runan Zhao; Songfeng Yu; Wenjun Wang; Donghong Liu (Food Research International, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

A powdery biohybrid nano‑silver sensor based on phycoerythrin and carbon nanotubes for visual detection of Hg2+ in aquatic products - Chuanxu Liu; Xiangyu Lan; Changzhuo Zheng; Qinghao Ge; Xiaolong Han; Yang Pu; Wenjun Li (Algal Research, 2026)

Evaluation of effects of presence of toluene and methanol on hydrophobic m-xylene removal in a biotrickling filter - Jia Liu; Jiamei Zheng; Yueyang Han; Wenjun Liang (Journal of Environmental Chemical Engineering, 2026)

Coating starch improves the quality of “Pepper-salt Pleurotus ostreatus”: Insights from rheologicalproperties, microstructure and water–oil distribution - Han Xie; Wenfeng Li; Zhenan Rao; Jichun Zhao; Fuhua Li; Wenjun Wang; Jian Ming (Food Chemistry, 2026)

Association between serum metal exposure in early pregnancy and preterm birth: Mediation by inflammatory blood cell parameters - Wenjun Yao; Luodan Zhang; Ziyi Wang; Weiguo Yao; Wanxin Wu; Fa Zeng; Maozhen Han; Peng Zhu; Fangbiao Tao; Fang Deng; Jian V. Zhang; Binbin Huang (Journal of Hazardous Materials, 2026)

Phase behaviour of lactoferrin and β-lactoglobulin complexes: Revealing mechanisms from an integrated experimental and theoretical perspective - Tianrong Wang; Tiantian Chen; Jing Ming; Qingbo Jiao; Jiayi Han; Hao Li; Zhijun Song; Gerui Ren; Min Huang; Qunfang Lei; Wenjun Fang; Zexing Cao; et al. (Food Hydrocolloids, 2026)

Mediating role of the maternal placental growth factor levels on association between ozone exposure and adverse pregnancy outcomes - Yajuan Wang; Yuanyuan Yu; Yang Li; Xiaoli Gao; Wenjun Fan; Xuening Bai; Xiaozhou Li; Jiayan Zhou; Ying Zhang; Qisijing Liu; Chen Li; Rongrong Wu; et al. (Environmental Research, 2026)

A sequentially activatable DNAzyme nanosystem for augmented tumor gene silencing and radiosensitization - Han Wu; Xianzhou Cai; Hao Jiang; Qin Fan; Jifeng Li; Wenjun Zhu; Longyu Zhao; Yingjie Ren; Ziliang Dong; Lianhui Wang (Chemical Engineering Journal, 2026)

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

Constructing spatially separated redox active sites over cyano-Sb-Trz for the cooperative coupling of hydrogen peroxide photosynthesis and benzyl alcohol upgrading - Han Wang; Haoyang Ma; Wenjun Jiang; Tiantian Yang; Su Zhan; Yinhua Ma; Feng Zhou (Journal of Environmental Chemical Engineering, 2026)

A central Tibetan highland during the Late Jurassic: Insights from sedimentology, provenance and detrital zircon trace element of the Xueshan Formation in the Qiangtang Basin - Jiawei Zhang; Zhongpeng Han; Yalin Li; Jiarun Tu; Jingen Dai; Xingduo Ma; Zijian Li; Zhihao He; Shuai Li; Wenjun Bi (Global and Planetary Change, 2026)

Paleocene to Eocene deformation and crustal shortening history of the Tanggula Range, Central Tibet - Wenjun Bi; Yalin Li; Zhongpeng Han; Chengshan Wang; Jiawei Zhang; Tiankun Xu; Dawei Lv; Chan Wang; Zining Ma; Haiyang He; Huan Chen (Global and Planetary Change, 2026)

An ODE-based multi-resolution parallel network for respiratory motion estimation - Ziming Zhang; Mingxiao Li; Wenjun Tan; Tianming Li; Ye Yuan; Juntao Han; Xinfeng Xu; Quan Zhu; Zhe Wang; Ruoyu Wang (Medical & Biological Engineering & Computing, 2026)

Multi-Scale Pore System and Its Implication for Shale Oil Occurrence in Alkaline Lacustrine Mixed Sedimentary Shale Reservoirs: A Case Study from Fengcheng Formation, Mahu Sag, Junggar Basin - Yuanhao Zhang; Zhenxue Jiang; Jiaqi Chang; Zhiye Gao; Liliang Huang; Wenjun He; Chengju Zhang; Lei Chen; Qingqing Fan; Yunhao Han; Bolin Zhang; Chao Chen (Journal of Earth Science, 2026)

Genome-wide identification and functional characterization of rapid alkalinization factor 6 as a key peptide regulator of abiotic stress tolerance in Tartary buckwheat - Wenjun Sun; Yuxing Qin; Yuting Cao; Jianliu Tong; Linyuan Shi; Han Liu; Gujing Wang; Xiaoqin Zheng; Liang Zou; Liangzhen Jiang; Changying Liu; Dabing Xiang (Plant Science, 2026)

Exploring the dynamic characteristics of LNG shipping network resilience by integrating complex network and SIR simulation: A case of China - Yulan Zhao; Xiaoxue Ma; Weiliang Qiao; Bing Han; Wenjun zhang (Ocean Engineering, 2026)

Lentinula edodes-derived exosome-like nanoparticles improve curcumin stability and biotransformation via gut microbiota interactions - Zhengmei Ji; Wenjun Ma; Pengfei Liang; Junjie Zhou; Ning Wang; Yuxin Guo; Miao Zhao; Yue Li; Yurong Guo; Yanhui Han (Food Chemistry, 2026)

Flavor improvement in enzymatically hydrolyzed Citrus Huyou peel residues: based on sensory and multi-omics analysis - Jiabao Huang; Xinyue Zhou; Han Wang; Qiong Huang; Jinting Li; Cheng Zeng; Wenjun Wang; Donghong Liu (Food Chemistry, 2026)

Factors influencing 3PLs’ willingness to adopt sustainable and resilient service strategies under climate change context - Jiaxiang Zhu; Wenjun Han; Feng Dong; Linxu Shi (Journal of Cleaner Production, 2025)

Impact of regionally transported biomass burning on carbonaceous aerosol characterization, contribution and degradation in Pu'er, Southwest China - Jianwu Shi; Wenjun Rao; Chenyang Zhao; Li Deng; Xinyu Han; Wei Du; Jianhong Huang; Senlin Tian; Ping Ning; Jiming Hao; Yaoqian Zhong (Journal of Environmental Sciences, 2025)

A multi-task deep attention network for simultaneous rapid quantification of sucrose, glucose, and fructose contents in pumpkin using FT-NIR spectroscopy - Yingchao Xu; Jiayu Luo; Shudan Xue; Huihui Han; Wenlong Luo; Wenjun Liu; Qingmin Jin; Huijing Lin; Baoling Chen; Yingyin Lin; Rong Zhang; Yujuan Zhong (Food Chemistry, 2025)

Relationship between microbial community and environmental factors in the sediments of the perennial backwater region of the three gorges reservoir - Chang Han; Xiaomin Wang; Zhiyuan Chen; Yue Chen; Wangmin Zhou; Shumeng Lu; Wenjun Yang (Ecohydrology & Hydrobiology, 2025)

A High-Resolution Mirror Migration Framework for Ocean Bottom Cable Seismic Data - Wenjun Ni; Shaoyong Liu; Mingyuan Xu; Bingkai Han; Guodong Fan (Journal of Marine Science and Engineering, 2025)
Seismic data migration is a critical step for accurate subsurface imaging. While Ocean Bottom Cable (OBC) surveys provide high-quality seismic data, reliance on primary reflections alone leads to significant illumination gaps. Receiver-side ghost waves can mitigate these gaps; however, conventional mirror migration suffers from low resolution and amplitude inaccuracy. To address these limitations, this study introduces a high-resolution mirror migration framework based on Point Spread Function (PSF)-guided inversion imaging. The methodology involves first separating the OBC wavefield to isolate ghost-wave components, followed by applying standard mirror migration to produce an initial, blurred image. Subsequently, the PSFs of down-going ghost waves are estimated to characterize imaging distortions, and image-domain least squares migration (LSM) is implemented via PSF deconvolution to reconstruct high-resolution reflectivity. Numerical experiments on complex models demonstrate that the proposed method preserves the additional illumination provided by this wavefield, substantially improves the spatial resolution of imaging targets, and enhances lateral continuity. Quantitative analysis confirms this enhancement through a significant extension of the effective vertical wavenumber bandwidth and the recovery of higher-frequency content. The framework provides a robust and computationally efficient solution for high-fidelity OBC imaging, enabling more reliable subsurface interpretation.

Colon health benefits of plant-derived exosome-like nanoparticles via modulating gut microbiota and immunity - Yanhui Han; Xiaojing Guo; Zhengmei Ji; Yuxin Guo; Wenjun Ma; Hengjun Du; Yurong Guo; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2025)

Potential applications of lipases rational design in the synthesis of medium- and long-chain triglycerides: Current advances and perspectives - Yiran Han; Hao Fang; Xiaoyu Nie; Xuanling Zhang; Zeping Lu; Binbin Nian; Yi Hu; Wenjun Cheng (Food Chemistry, 2025)

MWCNT-OH/PDMS elastomer-based microwave absorber with high-performance thermal stability and mechanical sensing properties - Jialiang Chen; Kaixi Bi; Shuqi Han; Hao Liu; Wenjun He; Yifan Li; Guangchen Yin; Wenqi Xiong; Linyu Mei; Xiujian Chou (Chemical Engineering Journal, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Dual-sulfur defects decorated 1T-WS2/Cd0.5Zn0.5S heterojunctions for boosted photocatalytic hydrogen evolution - Mei Dong; Wenjun Li; Liang Geng; Ruixue Huang; Hongli Han; Yuan Liu (Journal of Environmental Chemical Engineering, 2025)

Research on Ship Type Decision-Making for General Cargo Ship Owners Under Capacity Iteration: A TOPSIS Method Based on Agent Scoring - Wenjun Han; Xianhua Wu; Huai Deng (Journal of Marine Science and Engineering, 2025)
This study quantifies ship-type performance indicators by training intelligent agents to evaluate and score vessels. The Analytic Hierarchy Process (AHP) is then applied to assess the internal consistency of the collected data, ensuring its authenticity and validity. Subsequently, the entropy weight method is employed to objectively determine the significance of each indicator in ship-type decision-making. Finally, COSCO (China COSCO Shipping Corporation Limited) Shipping’s capacity gap reflects the results of the methodology: the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) technique ranks all feasible ship-type combinations, presenting their relative merits through quantitative results. A standardized grading system is further proposed to evaluate these combinations systematically. Ultimately, the 10 most suitable solutions are identified—none achieving the theoretical maximum rating of Grade 10—demonstrating room for improvement in vessel performance.

A thermal-hydro-mechanical coupled analysis model for climate-driven movements of valley glaciers (THM-GA 1.0) - Ruochen Jiang; Limin Zhang; Wenjun Lu; Dalei Peng; Xin He; Shihao Xiao; Yingyue Han; Mingdong Wei (Engineering Geology, 2025)

A monocular thoracoscopic 3D scene reconstruction framework based on NeRF - Juntao Han; Ziming Zhang; Wenjun Tan; Yufei Wang; Mingxiao Li (Medical & Biological Engineering & Computing, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Late Quaternary vertical throw rates along the Gyaring Co fault in central Tibet - Duo Wang; Lichun Chen; Hong Chang; Shugang Kang; Yongshun Jia; Jinhua Du; Fei Han; Yanbao Li; Gongming Yin; Wenjun Zheng; Xulong Wang (Journal of Asian Earth Sciences, 2025)

An improved local coarsening method for discrete element simulation on cracking propagation in rock and rock-like materials - Guansheng Han; Shaoqi Wang; Yu Zhou; Bo Li; Wenjun Lv; Weiqiang Chen; Qiongqiong Tang (Computers and Geotechnics, 2025)

Late Pleistocene palynological records from the Qaidam Basin (North Tibet) and their implications for Qarhan Lake evolution - Xue Ke; Fang Han; Xudong Bai; Tinglu Yang; Taizhong Song; Zongyan Zhang; Wenjun Yang; Jinming Zhang; Bowen Song (Journal of Asian Earth Sciences, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Variations in volatile components and biological activities of essential oils from Citrus aurantium ‘changshanhuyou’ at different growth and ripening stages - Han Wang; Xinyue Zhou; Yong Deng; Ruyu Zhang; Kai Fu; Jiabao Huang; Qiong Huang; Cheng Zeng; Donghong Liu; Wenjun Wang (Food Research International, 2024)

Chemical characteristics, sources, and formation mechanisms of PM2.5 before, during, and after the Spring Festival in a plateau city of Southwest China - Jianwu Shi; Li Deng; Wei Du; Xinyu Han; Yaoqian Zhong; Wenjun Rao; Haitao Xie; Feng Xiang; Ping Ning; Senlin Tian (Atmospheric Environment, 2024)

Host restriction factor Rab11a limits Porcine deltacoronavirus invasion of cells via fusion peptide-mediated membrane fusion - Cailiang Song; Hao Li; Yun Han; Kailu Wang; Wenjun Yan; Xin Yang; Anyun Zhang; Hongning Wang (Veterinary Microbiology, 2024)

The production of methyl mercaptan is the main odor source of chicken manure treated with a vertical aerobic fermenter - Majian Chen; Zhen Cao; Boyu Jing; Wenjun Chen; Xin Wen; Meng Han; Yan Wang; Xindi Liao; Yinbao Wu; Tao Chen (Environmental Research, 2024)

Identification of extracted antioxidants from Citrus aurantium 'Changshanhuyou' residue against digestive enzyme activities and airway smooth muscle cells proliferation using UPLC-MS/MS - Xinyue Zhou; Junyang Wang; Han Wang; Peng Lu; Qiong Huang; Ming Huang; Ruiling Lv; Donghong Liu; Wenjun Wang (Food Bioscience, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Distribution and community structure of antibiotic resistance genes in the Three Gorges Reservoir Area - Chang Han; Huiqun Cao; Haoyue Tan; Xiaomeng Li; Wenjun Yang (Environmental Science and Pollution Research, 2024)

Boosted scavenger-free photocatalytic H2O2 production over alkali-doped poly(heptazine imide) under controlled solution conditions - Ming Fang; Biao Wang; Guanhua Wan; Hui Cao; Chunfeng Wang; Peijiang Cao; Shun Han; Deliang Zhu; Wenjun Liu (Chemical Engineering Journal, 2024)

A strategy to boost xanthine oxidase and angiotensin converting enzyme inhibitory activities of peptides via molecular docking and module substitution - Pengfei Meng; Yanxin Wang; Yumeng Huang; Tong Liu; Mingxia Ma; Jiaojiao Han; Xiurong Su; Wenjun Li; Yanbo Wang; Chenyang Lu (Food Chemistry, 2024)

Hydrophilic phthalocyanine covalent organic frameworks for enhanced electrocatalytic H2O2 production - Rong Jiang; Qianjun Zhi; Bin Han; Ning Li; Kang Wang; Dongdong Qi; Wenjun Li; Jianzhuang Jiang (Chemical Engineering Journal, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Third-generation D-lactic acid production using red macroalgae Gelidium amansii by co-fermentation of galactose, glucose and xylose - Zhongyang Qiu; Guangli Wang; Wenjun Shao; Longyu Cao; Hufangguo Tan; Shuai Shao; Ci Jin; Jun Xia; Jianlong He; Xiaoyan Liu; Aiyong He; Xushen Han; et al. (Bioresource Technology, 2024)

Diagenetic evolution of tight sandstone and the formation of an effective reservoir in the lower member 3 of the Shahejie Formation, Bohai Bay Basin, East China - Xianxu Fang; Cunfei Ma; Lanquan Zhao; Liqing Lei; Wenjun Huang; Changcheng Han; Ming Qi (Marine and Petroleum Geology, 2024)

Effect of toluene on m-xylene removal in a biotrickling filter: Performance, biofilm characteristics, and microbial analysis - Jia Liu; Yueyang Han; Xiaona Dou; Wenjun Liang (Environmental Research, 2024)

Soil environment and annual rainfall co-regulate the response of soil respiration to different grazing intensities in saline-alkaline grassland - Huajie Diao; Jie Hao; Qianwen Yang; Yangyang Gao; Tengfei Ma; Fei Han; Wenjun Liang; Jie Chang; Likai Yi; Gaoliang Pang; Kuanhu Dong; Changhui Wang (CATENA, 2024)

Numerical Investigation on Interactive Hydrodynamic Performance of Two Adjacent Unmanned Underwater Vehicles (UUVs) - Xiaodong Liu; Yuli Hu; Zhaoyong Mao; Wenjun Ding; Shiyu Han (Journal of Marine Science and Engineering, 2023)
This study investigates the effectiveness of UUV formations during navigation to designated target areas. The research focuses on propeller-equipped UUVs and employs a computational fluid dynamics (CFD) methodology to analyze the hydrodynamic interactions among multiple UUV formations while en route to their targeted exploration areas. Utilizing the relative drag coefficients (rl and rf) and static thrust (Rfleets) as analytical parameters, this paper defines the relative distances (a and b) between UUVs within a formation and conducts a comparative analysis of the hydrodynamic performance between individual UUVs and formation configurations. The study establishes correlations between relative distances and the hydrodynamic performance of formations. The findings reveal the following: 1. For both the lead UUV and the following UUV within the formation, the rl and rf heatmaps exhibit two distinct regions: a thrust region and a drag region. Notably, these regions significantly overlap. The maximum rl is 31.23%, while the minimum rf is −20.9%, corresponding to relative distances of a = 0.12 and b = 1.5. Conversely, the minimum rl is −12.2%, while the maximum rf is 22.03%, with relative distances of a = 1.1 and b = 0.2; 2. An analysis of formation static thrust Rfleets reveals that it can be up to 7% greater than the drag experienced by self-propelled UUVs when relative distances a and b are set to 1.1 and 1, respectively. This highlights the enhanced performance achievable through formation navigation. The results presented in this paper offer valuable theoretical insights into the optimal design of relative distances within UUV formations, contributing to the advancement of UUV formation navigation strategies.

Roles of CeO2 in preparing Ce-doped CdIn2S4 with boosted photocatalytic degradation performance for methyl orange and tetracycline hydrochloride - Fengjue Wang; Wenjun Zhang; Han Liu; Ronggen Cao; Meng Chen (Chemosphere, 2023)

Water distribution based on SAR and optical data to improve hazard mapping - Yang Han; Fan Deng; Jie Gong; Zhiyuan Li; Ziyang Liu; Jing Zhang; Wenjun Liu (Environmental Research, 2023)

Multi-aspect study of an innovative glycerol-fed polygeneration model involving combined power cycles, chilled water unit, desalination, and methanol synthesis - Suhong Liu; Tao Hai; Bhupendra Singh Chauhan; Muhammad Asadollahzadeh; Mowffaq Oreijah; Kamel Guedri; Wenjun Han (Desalination, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Ultrasound-induced cell disintegration and its ultrastructure characterization for the valorisation of Chlorella pyrenoidosa protein - Yong Deng; Xiaoling Yang; Tianyi Yan; Weidong Xu; Jiaheng Li; Ruihao Niu; Runan Zhao; Han Wang; Hao Wang; Tingting Chen; Mingming Guo; Wenjun Wang; et al. (Bioresource Technology, 2023)

New failure criterion for rock slopes with intermittent joints based on energy mutation - Yu Zhou; Wenjun Lv; Zihan Zhou; Qiongqiong Tang; Guansheng Han; Jianshuai Hao; Weiqiang Chen; Faquan Wu (Natural Hazards, 2023)

Efficient photoelectrochemical aptasensing of di-2-ethylhexyl phthalate in environmental samples based on N, S co-doped graphene quantum dots/TiO2 nanorods - Dongyun Liao; Jinfeng Zhi; Qiang Wang; Wenjun Yan; Yujing Guo; Yujie Han; Chuan Dong; Yong Xiao; Hongcun Bai; Wenting Liang; Lifang Fan (Analytica Chimica Acta, 2023)

Visual analysis of global air pollution impact research: a bibliometric review (1996–2022) - Yanli Cao; Xianhua Wu; Wenjun Han; Jiaqi An (Environmental Science and Pollution Research, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Development and validation of a routine blood parameters-based model for screening the occurrence of retinal detachment in high myopia in the context of PPPM - Shengjie Li; Meiyan Li; Jianing Wu; Yingzhu Li; Jianping Han; Wenjun Cao; Xingtao Zhou (EPMA Journal, 2023)

Screening and characterization of sex-specific markers by NGS sequencing in Spinibarbus hollandi with implication of XY sex determination system - Chong Han; Wenwei Huang; Suhan Peng; Jiangwei Zhou; Huawei Zhan; Lin Gui; Wenjun Li; Qiang Li (Aquaculture, 2023)

Associations between serum polychlorinated biphenyls, halogen flame retardants, and renal function indexes in residents of an e-waste recycling area - Ling-Chuan Guo; Zhanlu Lv; Tingting Zhu; Guanhao He; Jianxiong Hu; Jianpeng Xiao; Tao Liu; Shengbing Yu; Jinliang Zhang; Han Zhang; Wenjun Ma (Science of The Total Environment, 2023)

Recognition of Unsafe Onboard Mooring and Unmooring Operation Behavior Based on Improved YOLO-v4 Algorithm - Changjiu Zhao; Wenjun Zhang; Changyuan Chen; Xue Yang; Jingwen Yue; Bing Han (Journal of Marine Science and Engineering, 2023)
In the maritime industry, unsafe behaviors exhibited by crew members are a significant factor contributing to shipping and occupational accidents. Among these behaviors, unsafe operation of mooring lines is particularly prone to causing severe accidents. Video-based monitoring has been demonstrated as an effective means of detecting these unsafe behaviors in real time and providing early warning to crew members. To this end, this paper presents a dataset comprising videos of unsafe mooring line operations by crew members on the M.V. YuKun. Additionally, we propose an unsafe behavior recognition model based on the improved You Only Look Once (YOLO)-v4 network. Experimental results indicate that the proposed model, when compared to other models such as the original YOLO-v4 and YOLO-v3, demonstrates a significant improvement in recognition speed by approximately 35% while maintaining accuracy. Additionally, it also results in a reduction in computation burden. Furthermore, the proposed model was successfully applied to an actual ship test, which further verifies its effectiveness in recognizing unsafe mooring operation behaviors. Results of the actual ship test highlight that the proposed model’s recognition accuracy is on par with that of the original YOLO-v4 network but shows an improvement in processing speed by 50% and a reduction in processing complexity by about 96%. Hence, this work demonstrates that the proposed dataset and improved YOLO-v4 network can effectively detect unsafe mooring operation behaviors and potentially enhance the safety of marine operations.

Active chitosan/gum Arabic-based emulsion films reinforced with thyme oil encapsulating blood orange anthocyanins: Improving multi-functionality - Runan Zhao; Jin Chen; Songfeng Yu; Ruihao Niu; Zhehao Yang; Han Wang; Huan Cheng; Xingqian Ye; Donghong Liu; Wenjun Wang (Food Hydrocolloids, 2023)

Impacts of the Urban Spatial Landscape in Beijing on Surface and Canopy Urban Heat Islands - Yonghong Liu; Yongming Xu; Yeping Zhang; Xiuzhen Han; Fuzhong Weng; Chunyi Xuan; Wenjun Shu (Journal of Meteorological Research, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

High-precision potassium isotope analysis using the Nu Sapphire collision cell (CC)-MC-ICP-MS - Wenjun Li; Mengmeng Cui; Qiqi Pan; Jing Wang; Bingyu Gao; Shanke Liu; Meng Yuan; Benxun Su; Ye Zhao; Fang-Zhen Teng; Guilin Han (Science China Earth Sciences, 2022)

The Epigenetic Regulation of OLIG2 by Histone Demethylase KDM6B in Glioma Cells - Aixia Sui; Biaogang Han; Wenjun Ren; Weiliang He; Chao Gao; Xiaohui Han; Shifeng Liu; Yan Zhang; Xueling Qi; Xiaoqiang Guo (Journal of Molecular Neuroscience, 2022)

Association between ozone exposure and prevalence of mumps: a time-series study in a Megacity of Southwest China - Wenjun Xie; Han Zhao; Chang Shu; Bin Wang; Wen Zeng; Yu Zhan (Environmental Science and Pollution Research, 2021)

Identification of cryptic putative IRESs within the ORF encoding the nonstructural proteins of the human rhinovirus 16 genome - Bingtian Shi; Qinqin Song; Xiaonuan Luo; Juan Song; Dong Xia; Zhiqiang Xia; Mi Liu; Wenjun Wang; Ruifang Wang; Haijun Du; Jun Han (Archives of Virology, 2021)

Deformation and cooling history of the Central Qiangtang terrane, Tibetan Plateau and its tectonic implications - Wenjun Bi; Zhongpeng Han; Yalin Li; Chengming Li; Chengshan Wang; Jiawei Zhang; Jianyun Han; Haiyang He; Xinyu Qian; Tiankun Xu; Zining Ma (International Geology Review, 2021)

Short-term effects of soil moisture on soil organic carbon decomposition in a coastal wetland of the Yellow River Delta - Wendi Qu; Guangxuan Han; Jian Wang; Juanyong Li; Mingliang Zhao; Wenjun He; Xinge Li; Siyu Wei (Hydrobiologia, 2021)

Aquiflexum lacus sp. nov., isolated from a lake sediment sample - Jianrong Huang; Mingxian Han; Baozhu Fang; Jian Yang; Haiyi Xiao; Xiying Zhang; Jibin Han; Dongmei Yu; Hongchen Jiang; Wenjun Li (Archives of Microbiology, 2021)

Influence of the urban spatial layout of central Beijing on the atmospheric humidity field - Yonghong Liu; Yongming Xu; Xiuzhen Han; Wenjun Shu; Fuzhong Weng (Theoretical and Applied Climatology, 2021)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

In vitro induction and characterization of hexaploid Pennisetum × advena, an ornamental grass - Yuesen Yue; Xifeng Fan; Yaofang Hu; Chao Han; Hui Li; Wenjun Teng; Hui Zhang; Ke Teng; Haifeng Wen; Xuejun Yang; Juying Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effects of the last glacial period on genetic diversity and genetic differentiation in Cryptomeria japonica in East Asia - Yoshihiko Tsumura; Megumi Kimura; Katsuhiro Nakao; Kentaro Uchiyama; Tokuko Ujino-Ihara; Yafeng Wen; Zaikang Tong; Wenjun Han (Tree Genetics & Genomes, 2020)

Fipronil induces apoptosis and cell cycle arrest in porcine oocytes during in vitro maturation - Wenjun Zhou; Ying-Jie Niu; Zheng-Wen Nie; Yong-Han Kim; Kyung-Tae Shin; Jing Guo; Xiang-Shun Cui (Apoptosis, 2019)

Evaluating Algeria’s social and economic development using a series of night-time light images between 1992 to 2012 - Xi Li; Lixian Zhao; Wenjun Han; Bouarouri Faouzi; Prosper Washaya; Xubing Zhang; Huazhong Jin; Chuanqing Wu (International Journal of Remote Sensing, 2018)

Calcium carbonate precipitation by Synechocystis sp. PCC6803 at different Mg/Ca molar ratios under the laboratory condition - Zuozhen Han; Ruirui Meng; Huaxiao Yan; Hui Zhao; Mei Han; Yanyang Zhao; Bin Sun; Yanbiao Sun; Jie Wang; Dingxiang Zhuang; Wenjun Li; Lingxue Lu (Carbonates and Evaporites, 2017)

Deletion of a non-catalytic region increases the enzymatic activity of a β-agarase from Flammeovirga sp. MY04 - Wenjun Han; Jingyan Gu; Huihui Liu; Fuchuan Li; Zhihong Wu; Yuezhong Li (Journal of Ocean University of China, 2015)

Knockdown of response gene to complement 32 (RGC32) induces apoptosis and inhibits cell growth, migration, and invasion in human lung cancer cells - Ran Xu; Chao Shang; Jungang Zhao; Yun Han; Jun Liu; Kuanbing Chen; Wenjun Shi (Molecular and Cellular Biochemistry, 2014)

A Combined Dry Jet Mixing-Prefabricated Vertical Drain Method for Soft Ground Improvement: A Case Study - Zhang Dingwen; Liu Songyu; Han Wenjun; Du Guangyin (Marine Georesources & Geotechnology, 2013)

A polysaccharide-degrading marine bacterium Flammeovirga sp. MY04 and its extracellular agarase system - Wenjun Han; Jingyan Gu; Qiujie Yan; Jungang Li; Zhihong Wu; Qianqun Gu; Yuezhong Li (Journal of Ocean University of China, 2012)

Expression of a Suaeda salsa Vacuolar H+/Ca2+ Transporter Gene in Arabidopsis Contributes to Physiological Changes in Salinity - Ning Han; Wenjun Lan; Xi He; Qun Shao; Baoshan Wang; Xinjie Zhao (Plant Molecular Biology Reporter, 2012)

Influence of Novel Nano-Mesoporous Bioactive Glass on the Regulation of IGF-II Gene Expression in Osteoblasts - Zhang Quan; Xie Han; Zhang Ye; Yu Chenzhong; Chen Wenjun (Cell Biochemistry and Biophysics, 2012)